Comparative study of bi-2223 synthesised via electrospinning and coprecipitation methods - Bryan Andrew, Balasan (2021)
Ceramic superconducting materials could enhance the efficiency of electronics, however, there are issues such as low current density and the requirements of cooling this material to achieve Meissner effect which hinders superconductivity. This can be rectified either with addition or substitutes of foreign rare earth elements to the material to modify their properties. The objective of the research was to synthesise bismuth-based superconductor Bi2Sr2Ca2Cu3O10 (Bi-2223) via electrospinning, characterisation of thermal, structural and electrical transport properties of samples, and lastly to study the effect of Pb addition unto precursors of samples. For this research, electrospinning has downsized the grains of samples, and samples prepared via coprecipitation was compared with the electrospun samples to investigate their critical temperature, activation energy and current density. The electrospun samples were expected to exhibit grain morphology advantage over coprecipitation prepared samples to enhance the problem of low current density present in superconductors stemming from weak intergrain links of grain boundaries. The samples were characterised via the naked eye, thermal analysis, electron imaging, crystallography analysis, four-point probe method and magnetic susceptibility. The electrospun samples (ES) investigated via electron imaging for pellet form had abundancy of low angled grain boundaries when compared with coprecipitation prepared samples (COP). Critical temperatures of P-COP-2223, P-ESPb-2223 and P-ES-2223 achieved at 98 K, 80 K and 68 K respectively. This was due to volume fraction of Bi-2223 phase in the electrospun samples being lower than of coprecipitated samples. The current density measurement for P-COP-2223 led with 4928 A/cm2, then P-ESPb-2223 with 1852 A/cm 2 whereas P-ES-2223 not obtainable due to low angled grain boundaries and the instrument’s low sensitivity. This research contributes to the effect of grain boundaries by synthesising a denser grain boundary at the expense of weaker pinning centres which proves the capability of synthesising Bi-2223 with electrospinning method.